2023
DOI: 10.3390/plants12051198
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Evolutionary Analysis of Gossypium YTH Domain-Containing RNA-Binding Protein Family and the Role of GhYTH8 in Response to Drought Stress

Abstract: YTH domain-containing proteins are one kind of RNA-binding protein involved in post-transcriptional regulation and play multiple roles in regulating the growth, development, and abiotic stress responses of plants. However, the YTH domain-containing RNA-binding protein family has not been previously studied in cotton. In this study, a total of 10, 11, 22, and 21 YTH genes were identified in Gossypium arboreum, Gossypium raimondii, Gossypium barbadense, and Gossypium hirsutum, respectively. These Gossypium YTH g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It was reported that the trehalose-6phosphate synthase gene family played a key role in metabolic regulation and abiotic stress (F. Xie et al, 2014). In the same way, about 41% of genes of the F-box family were speculated to be without introns in Oryza sativa and 45% in Arabidopsis (Gálvez et al, 2012;Hao et al, 2023). Reverse transcription, duplication, and integration possibly caused intron loss from genes in plants (Y.…”
Section: Gene Ontologymentioning
confidence: 99%
“…It was reported that the trehalose-6phosphate synthase gene family played a key role in metabolic regulation and abiotic stress (F. Xie et al, 2014). In the same way, about 41% of genes of the F-box family were speculated to be without introns in Oryza sativa and 45% in Arabidopsis (Gálvez et al, 2012;Hao et al, 2023). Reverse transcription, duplication, and integration possibly caused intron loss from genes in plants (Y.…”
Section: Gene Ontologymentioning
confidence: 99%